Search for scalar leptoquark pairs decaying to electrons and jets in p̄ p collisions - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amidi, E; Amos, N; Anderson, E; et al. (1997)
We have searched for the pair production of first generation scalar leptoquarks in the eejj channel using the full data set (123 pb-1) collected with the DO detector at the Fermilab Tevatron during 1992-1996. We observe no candidates with an expected background of approximately 0.4 events. Comparing the experimental 95% confidence level upper limit to theoretical calculations of the cross section with the assumption of a 100% branching fraction of eq, we set a lower limit on the mass of a first generation scalar leptoquark of 225 GeV/c2. The results of this analysis rule out the interpretation of the excess of high Q2 events at DESY HERA as leptoquarks which decay exclusively to eq.